Studi Kandungan Logam Berat (As, Cd, Cr, Pb Dan Hg) dalam Particulate Matter 10 Mikron (PM10) di Beberapa Ruas Jalan Kota Medan - Isra' Suryati; M Nasri Akbar; Nurrakhmah Latifah (Jurnal Dampak, 2019)
The increase in population is directly proportional to the increase in transportation facilities. Medan city as one of the metropolitan cities also experienced an increase in the number of vehicles ± 0.6% / year. Motorized vehicles are one source of emissions in reducing urban air quality. One parameter that has a direct impact on health is particulate matter of 10 microns (PM10). This study aims to analyze the content of heavy metals (As, Cd, Cr, Hg and Pb) in PM10 from direct measurements on SM Raja Street, Balai Kota Street and Pinang Baris Street. Analysis of heavy metal content in PM10 is carried out by Inductively Coupled Plasma (ICP). Based on the observation of traffic volume in these 3 (three) roads, the highest number of vehicles is on SM Raja Street which is 8,417 units/hour (morning) and 10,043 units/hour (afternoon). The high number of vehicles on SM Raja Street because this road is a cross-province road. PM10 measurement results are 271,505 μg/Nm3 on SM Raja Street, 92,75 μg/Nm3 at Pinang Baris Street and 85,035 μg/Nm3 at Balai Kota Street. When compared with the national ambient air quality standard (150 μg / Nm3) which exceeds the quality standard is SM Raja Street. The content of some heavy metals in PM10 on several roads in Medan City for As parameters (0.57 - 1.80 μg/Nm3), Cd (1.97 - 3.63 μg/Nm3), Cr (0.08 - 0, 15 μg/Nm3), Hg (0.57 - 0.99 μg/Nm3) and Pb (0.45 - 0.63 μg/Nm3). One way to reduce heavy metal content in PM10 is to increase the area of green open space in Medan City.Keywords: Heavy metals, PM10, area of green, transportation ABSTRAKPeningkatan populasi berbanding lurus dengan peningkatan fasilitas transportasi. Kota Medan sebagai salah satu kota metropolitan juga mengalami peningkatan jumlah kendaraan ± 0,6% / tahun. Kendaraan bermotor adalah salah satu sumber emisi dalam mengurangi kualitas udara perkotaan. Salah satu parameter yang memiliki dampak langsung terhadap kesehatan adalah partikel 10 mikron (PM10). Penelitian ini bertujuan untuk menganalisis kandungan logam berat (As, Cd, Cr, Hg dan Pb) di PM10 dari pengukuran langsung di Jalan SM Raja, Jalan Balai Kota dan Jalan Pinang Baris. Analisis kandungan logam berat dalam PM10 dilakukan oleh Inductively Coupled Plasma (ICP). Berdasarkan pengamatan volume lalu lintas di 3 (tiga) jalan ini, jumlah kendaraan tertinggi adalah di Jalan SM Raja yaitu 8.417 unit / jam (pagi) dan 10.043 unit / jam (sore). Tingginya jumlah kendaraan di Jalan SM Raja karena jalan ini merupakan jalan lintas provinsi. Hasil pengukuran PM10 adalah 271.505 μg / Nm3 di Jalan SM Raja, 92,75 μg / Nm3 di Jalan Pinang Baris dan 85.035 μg / Nm3 di Jalan Balai Kota. Jika dibandingkan dengan standar kualitas udara ambien nasional (150 μg / Nm3) yang melebihi standar kualitas adalah Jalan SM Raja. Kandungan beberapa logam berat dalam PM10 pada beberapa jalan di Kota Medan untuk parameter As (0,57 - 1,80 μg / Nm3), Cd (1,97 - 3,63 μg / Nm3), Cr (0,08 - 0, 15 μg / Nm3), Hg ( 0,57 - 0,99 μg / Nm3) dan Pb (0,45 - 0,63 μg / Nm3). Salah satu cara untuk mengurangi kandungan logam berat di PM10 adalah dengan meningkatkan area ruang terbuka hijau di Kota Medan.Kata Kunci: logam berat, PM10, terbuka hijau, transportasi